IMPLEMENTASI STORYTELLING DALAM PEMBELAJARAN SKI UNTUK MENANAMKAN NILAI KETELADANAN SAHABAT NABI PADA SISWA KELAS IV MI/SD - Akna, Irnaini; Aprilia Setia Ningrum; Zanuba Habsah Sonia Aunur Rofiah; Fenny Arista; Nailatul Hidayah; Atiul Maula; Inamul Maidatus Salwa; Dian Rifiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Understanding and instilling the exemplary values of the Prophet's companions in the learning of Islamic Cultural History (SKI) in grade IV MI/SD is still low and is still dominated by the lecture method. This study aims to determine the implementation of the storytelling method and its influence in instilling the exemplary values of the Prophet's companions in students. This study uses a qualitative approach with a case study type. Data collection techniques are carried out through observation and interviews. The results of the study show that the implementation of storytelling is able to create more interactive and enjoyable learning. Students become more active, enthusiastic, and easily understand the material presented. In addition, exemplary values such as honesty, responsibility, social care, and courage begin to be seen in students' daily behavior. Storytelling not only improves cognitive aspects, but is also effective in developing students' affective aspects. The storytelling method can be an effective learning alternative in SKI learning to instill character values in elementary school students.